Resolusi Konflik Agraria antara Masyarakat Adat Soge Natarmage dan Goban Runut-Tana AI dengan PT Kristus Raja Maumere di Desa Nangahale, Kabupaten Sikka - Febriana Emelda Soge; Ajis Salim Adang Djaha; Ardy Yosafat Pandie; Mariayani Oktaviana Rene (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2026)
Agrarian conflict remains one of the most persistent issues in Indonesia, particularly involving indigenous communities, government institutions, and private corporations. This study aims to analyze the dynamics of agrarian conflict, the role of agenda control in policymaking, and the effectiveness of conflict resolution between the Soge Natarmage and Goban Runut-Tana Ai Indigenous Communities and PT Kristus Raja Maumere (Krisrama) in Nangahale Village, Sikka Regency. This research employed a qualitative approach using a case study method. Data were collected through in-depth interviews, observation, and document analysis, and were analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings reveal that the conflict is rooted in competing claims between the company's formal Land Cultivation Rights (Hak Guna Usaha/HGU) and the indigenous communities’ historical claims over customary land. The conflict resolution process has been largely dominated by a legal-formal approach that prioritizes HGU legality, while the recognition of indigenous land rights has received limited attention. The study further identifies the presence of agenda control and nondecision making practices that influence the direction of conflict resolution policies. Moreover, mediation efforts have not adequately addressed the root causes of the conflict because they remain focused on administrative and legal aspects rather than the social, cultural, and historical dimensions of indigenous communities. The study concludes that sustainable agrarian conflict resolution requires a more inclusive, participatory, and equitable approach through the recognition of indigenous rights and the involvement of all stakeholders in policymaking processes.